2007
DOI: 10.1002/cne.21292
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and electrophysiological properties of hamster spinal dorsal horn neurons that express VGLUT2 and enkephalin

Abstract: The excitatory amino acid glutamate mediates transmission at spinal synapses, including those formed by sensory afferent fibers and by intrinsic interneurons. The identity and physiological properties of glutamatergic dorsal horn neurons are poorly characterized despite their importance in spinal sensory circuits. Moreover, many intrinsic spinal glutamatergic synapses colocalize the opioid peptide enkephalin (ENK), but the neurons to which they belong are yet to be identified. Therefore, we used immunohistoche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
21
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 85 publications
5
21
0
Order By: Relevance
“…In this study, simultaneous whole cell recordings were made between synaptically connected pairs of neurons in spinal lamina III and IV where collateral branches of slowly and rapidly adapting mechanoreceptor afferent fibers terminate. The present results are consistent with our previous studies suggesting that LIII/IV interneurons are interconnected via excitatory synapses using glutamate as a transmitter or via inhibitory linkages mediated by release of GABA (Schneider and Lopez 2002;Schneider and Walker 2007). Synaptic connections between LIII and IV neurons are predominantly unidirectional, and the majority of these are inhibitory.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In this study, simultaneous whole cell recordings were made between synaptically connected pairs of neurons in spinal lamina III and IV where collateral branches of slowly and rapidly adapting mechanoreceptor afferent fibers terminate. The present results are consistent with our previous studies suggesting that LIII/IV interneurons are interconnected via excitatory synapses using glutamate as a transmitter or via inhibitory linkages mediated by release of GABA (Schneider and Lopez 2002;Schneider and Walker 2007). Synaptic connections between LIII and IV neurons are predominantly unidirectional, and the majority of these are inhibitory.…”
Section: Discussionsupporting
confidence: 93%
“…The present results are consistent with our previous finding that the VGLUT2 vesicular glutamate transporter, a specific and reliable marker of glutamatergic synapses, is localized within axon terminals of dorsal horn interneurons (Schneider and Walker 2007). Together these studies show that glutamate, acting on AMPA type receptors, mediates excitatory synaptic linkages between lamina III and IV interneurons.…”
Section: Chemical Mediators At Local Synaptic Linkagessupporting
confidence: 93%
See 1 more Smart Citation
“…The pattern of immunohistochemical labeling obtained with the guinea pig anti-VGLUT1 in rodent brain tissue was similar to that obtained with the rabbit anti-VGLUT1 (Persson et al, 2006;Bogen et al, 2006). Preabsorption of antisera with the immunogen synthetic peptide utilized to produce guinea pig anti-VGLUT2 antibodies eliminated the immunostaining in tissue sections from rat CNS (manufacturer's technical information) and in hamster spinal cord (Schneider and Walker, 2007). The pattern of rodent CNS staining was identical to that obtained by Fremeau et al (2001) with a polyclonal rabbit anti-VGLUT2 antibody.…”
Section: Antibody Specificitysupporting
confidence: 55%
“…Many neurons in the spinal cord are interneurons with processes that extend only few spinal segments (Kostyuk and Vasilenko, 1979). At least some of these interneurons express VGLUT2 (Hinckley et al, 2005;Bannatyne et al, 2006;Schneider and Walker, 2007) and thus could be the source of some of the VGLUT2-ir we observed in the spinal cord. As mentioned above, we and others (Pan et al, 1999;Schnell and Wessendorf, 2004) have found abundant MOR 1C mRNA throughout the spinal cord.…”
Section: Spinal Cordmentioning
confidence: 87%